Social Network Characteristics, Disability and Survival among Middle-Aged and Older Adults - Abuladze, Liili (Studies of Transition States and Societies, 2025)
Social support may affect survival for everyone, or it may buffer the effects of chronic strain. This paper explores whether, how, and which social network characteristics are associated with longer overall survival as well as longer survival when experiencing disability-related stress. The data used is from the SHARE Estonia survey for the population aged 50+ (2010–2020), cross-checked with the timing of death from the population register. The effects of six network characteristics were analysed: network size, frequency of contact with family members, number of children in the network, reporting a partner and friends as network members, and overall emotional closeness with the network. Network characteristics, disability, employment, legal marital status, and practical support were constructed as time-varying variables. Men and women were analysed separately using Cox’s hazard models. The analytical sample includes 2,754 people (1,157 men and 1,597 women) without everyday activity limitations at the onset, of whom 14.5% (19.9% of men and 10.5% of women) died during the observation period. The results show that irrespective of whether they experience stress, larger networks protect women from dying earlier. Frequency of contact with family members was the only significant factor buffering the experience of everyday activity limitations, albeit with high uncertainty and only among men.